Henri Louis Frédéric de Saussure's Linguistic-Semiotics and Nganan Firasat's Rhetoric - Amanda, Dhea; Selti; Mariani, Evi; Zain, Puji Efriany; Munte, Alfonso (Indonesian Scientific Publication, 2023)
This paper discusses premonitions with various meanings originating from the Ngaju Dayak Tribe. The text is free from grammatical errors, spelling mistakes, and punctuation errors. No changes in content have been made. Firasat, a type of folklore, is also a signifier based on daily experiences in the rivers and forests iconic to the island of Kalimantan. The language used is clear, objective, and value-neutral, with a formal register and precise word choice. The text adheres to conventional structure and formatting features, with consistent citation and footnote style. The sentences and paragraphs create a logical flow of information with causal connections between statements. Henri Louis Frédéric de Saussure researched the cultural richness as part of the vocal system, including language, tradition (grammaire générale), semiotics, and linguistic rhetoric. The research method analysed the linguistic study of premonitions in the context of Central Kalimantan through literature review (secondary sources) and interviews with three research subjects from Central Kalimantan as valid sources. The results indicate that Nganan Firasat has been a long-standing ritual, faithful and consistent to this day due to its embodiment of rich traditions. Not only is it a local tradition, but it also holds national and global significance, aligning with universal human values.